Effects of bromopride on the healing of left colonic anastomoses in rats with induced abdominal sepsis - Silva,Silvana Marques e (2012)
PURPOSE: To evaluate the effects of bromopride on the healing of left colonic anastomoses in rats with induced abdominal sepsis. METHODS: Forty rats were divided into two groups to receive either bromopride (experimental group- E) or saline (control group- C). Each group was divided into subgroups of ten animals each to be euthanized on third (E3 and C3) or seventh day (E7 and C7) after surgery. Sepsis was induced by cecal ligation and puncture. The rats underwent segmental left colon resection and end-to-end anastomosis. Adhesion formation, tensile strength and hydroxyproline concentration were assessed. Histomorphometry of collagen and histopathological analysis were also performed. RESULTS: On postoperative third day, anastomoses in bromopride-treated animals showed lower tensile strength (p=0.02) and greater reduction in hydroxyproline concentration (p=0.04) than in control animals. There was no statistical difference in these parameters on seventh day, and the remaining parameters were similar across subgroups. Collagen content was also similar across subgroups. CONCLUSION: In the presence of abdominal sepsis, the administration of bromopride was associated with decreased tensile strength and hydroxyproline concentration in left colonic anastomoses in rats three days after surgery.